Closed Mitral Valvotomy (as a Surgical Treatment Option) – Does it has any Medico Legal Bearings in the Present Scenario - Amit Chaudhary, Amit Singh2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction- A prospective study of closed Mitral Valvotomy in 104 patientsMethod and Result- From December 2012 to December 2019, 104 patients underwent CMV. 94 Patientsbecome symptom free after surgery and only 7 patients required Mitral valve replacement surgery on followupConclusion- Closed Mitral Valvotomy represents a satisfactory technique in terms of lower cost, highefficacy, simplicity and reproducibility